2020
DOI: 10.3390/cells9010150
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy in Alzheimer’s Disease and Other Age-Related Neurodegenerative Diseases

Abstract: Mitochondrial dysfunction is a central aspect of aging and neurodegenerative diseases, including Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis, and Huntington’s disease. Mitochondria are the main cellular energy powerhouses, supplying most of ATP by oxidative phosphorylation, which is required to fuel essential neuronal functions. Efficient removal of aged and dysfunctional mitochondria through mitophagy, a cargo-selective autophagy, is crucial for mitochondrial maintenance and neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(116 citation statements)
references
References 260 publications
(338 reference statements)
1
114
0
1
Order By: Relevance
“…Next, we examined whether Rheb‐associated mitophagy requires Nix, an outer mitochondrial membrane protein (Youle & Narendra, ; Cai & Jeong, ). Utilizing Nix shRNA that was previously described (Fei et al , ; Melser et al , ), we found that Nix RNAi results in markedly reduced localization of Rheb to axonal mitochondria upon Δψ m dissipation (Scrambled shRNA: 38.83% ± 1.34%; Nix shRNA: 23.31% ± 1.26%; P < 0.001; Fig EV1G and H).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we examined whether Rheb‐associated mitophagy requires Nix, an outer mitochondrial membrane protein (Youle & Narendra, ; Cai & Jeong, ). Utilizing Nix shRNA that was previously described (Fei et al , ; Melser et al , ), we found that Nix RNAi results in markedly reduced localization of Rheb to axonal mitochondria upon Δψ m dissipation (Scrambled shRNA: 38.83% ± 1.34%; Nix shRNA: 23.31% ± 1.26%; P < 0.001; Fig EV1G and H).…”
Section: Resultsmentioning
confidence: 99%
“…ATP is generated in the cells by mitochondria, which are known as the powerhouse of the cell, through the OXPHOS system. The energy supply is critical for the ATP-dependent neurotransmission in the nervous system, including the auditory system [ 16 ]. The function and morphology of the mitochondria decline with aging, which results in an energy deficit and age-dependent decline in organ function [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitophagy serves as a major quality control mechanism to remove aged and impaired mitochondria in neurons [ 16 ]. The disruption of mitophagy has been associated with various neurodegenerative disorders, including Alzheimer’s, Parkinson’s, and Huntington’s diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their peerless properties as postmitotic-differentiated cells, neurons are strongly dependent on the controlled clearance of impaired proteins and organelles. Efficient removal of aggregated proteins during the aging of the neurons and dysfunctional or aged organelles is essential to prevent elevated cellular stress and neurodegenerative mechanisms [ 97 , 100 ]. A decline in mitophagy impacts mitostasis and may lead to a deficient function of the postmitotic neuron and further to cell death [ 42 ].…”
Section: Autophagy and Mitophagy As A Crucial Cellular Mechanism Pmentioning
confidence: 99%